Analysis on the impact of grounding on the system stability against surge and lightning - Tsen, Henry Llewellyn Tze Henn (2021)
Human’s safety and electrical equipment protection are important where earthing system play a significant role against over voltages. The earthing system provides a low resistance path to earth by removing unwanted excessive electrical currents. The curren ts that caused by abnormal condition such as switching electrical supply. lightning The performance of earthing system contributed by a few factor or strike, fault and bad grounding is s such as soil resistivity or lack of awareness during initial earthing system design stage. Therefore, this thesis assesses system thru Matrix L aboratory the affect of earthing (MATLAB) software for simulation. earthing system solution also ev aluated, In addition Ground Enhancement Material (GEM) software is used for design , Computer Aided Design computation based on IEEE guidebook (AutoCAD) for design drawing. and Automatical The gathered results of the earthing system performance were validated based on other reference papers earthing performance as result can change the voltage rise in the systems.